PENGARUH GAYA HIDUP, KEPERCAYAAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN SHOPEE PAYLATER MASYARAKAT KOTA SURABAYA - Valdi Ramadhan Jaya Saputra; Tri Sudarwanto (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This research is to find out the variables of lifestyle, trust, and ease of influence partially on purchasing decisions using Shopee Paylater for the people of Surabaya city and also want to know the variables of lifestyle, trust, and ease of influencing simultaneously or jointly influencing purchasing decisions using the community's Shopee Paylater city ​​of Surabaya. This research uses descriptive quantitative. In this study, the population used by all Shopee Paylater users in the city of Surabaya used the